Macrophages drive KSHV B cell latency - Agnieszka Szymula; Gabriela Samayoa-Reyes; Sidney Ogolla; Bing Liu; Shijun Li; Athira George; Nicholas Van Sciver; Rosemary Rochford; J. Pedro Simas; Kenneth M. Kaye (Cell Reports, 2023)
Summary: Kaposi’s sarcoma herpesvirus (KSHV) establishes lifelong infection and persists in latently infected B cells. Paradoxically, in vitro B cell infection is inefficient, and cells rapidly die, suggesting the absence of necessary factor(s). KSHV epidemiology unexpectedly mirrors that of malaria and certain helminthic infections, while other herpesviruses are ubiquitous. Elevated circulating monocytes are common in these parasitic infections. Here, we show that KSHV infection of monocytes or M-CSF-differentiated (M2) macrophages is highly efficient. Proteomic analyses demonstrate that infection induces macrophage production of B cell chemoattractants and activating factor. We find that KSHV acts with monocytes or M2 macrophages to stimulate B cell survival, proliferation, and plasmablast differentiation. Further, macrophages drive infected plasma cell differentiation and long-term viral latency. In Kenya, where KSHV is endemic, we find elevated monocyte levels in children with malaria. These findings demonstrate a role for mononuclear phagocytes in KSHV B cell latency and suggest that mononuclear phagocyte abundance may underlie KSHV’s geographic disparity.